Assessing environmental and human health risks of pharmaceutical contamination in surface water - Ioana-Antonia Cimpean; Florentina Laura Chiriac; Diana Constantinescu-Groposila; Victor Constantin Cojocaru; Vasile Ion Iancu (Romanian Journal of Ecology & Environmental Chemistry)
Pharmaceuticals, also known as medicines, are a mixture of substances used to prevent and treat human or animal diseases or infections. These products are used in many areas, such as medicine, aquaculture, animal husbandry, and, not least, in people’s everyday lives. According to the literature, they are classified into several therapeutic classes, the ones of interest for this paper being non-steroidal anti-inflammatory drugs; antidiabetic drugs, and antacid drugs. The mentioned drugs have raised concerns due to their presence in the environment and the potential health risks they pose. Recently, much research has focused on compounds that have direct harmful effects but are found in the environment at relatively low concentrations. These compounds could seriously threaten aquatic ecosystems, especially in the long term, due to their ability to accumulate in living organisms through bioaccumulation or generate secondary metabolites with harmful side effects. To effectively monitor pharmaceuticals in the environment, it is essential to have a variety of rapid, reliable, and sensitive methods capable of detecting numerous compounds. The most commonly employed techniques include solid phase extraction (SPE) followed by high-performance liquid chromatography coupled with mass spectrometry (HPLC/MS). This study supports ongoing efforts to monitor and regulate drug contamination in water sources, evaluating potential risks to human health and emphasizing the importance of addressing these contaminants to protect environmental and public health.